2000
DOI: 10.1016/s0002-9440(10)64828-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of Experimental Malignant Pleural Effusions Is Dependent on Invasion of the Pleura and Expression of Vascular Endothelial Growth Factor/Vascular Permeability Factor by Human Lung Cancer Cells

Abstract: We determined the molecular mechanisms that regulate the pathogenesis of malignant pleural effusion (PE) associated with advanced stage of human, non-small-cell lung cancer. Intravenous injection of human PC14 and PC14PE6 (adenocarcinoma) or H226 (squamous cell carcinoma) cells into nude mice yielded numerous lung lesions. PC14 and PC14PE6 lung lesions invaded the pleura and produced PE containing a high level of vascular endothelial growth factor (VEGF)-localized vascular hyperpermeability. Lung lesions produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 27 publications
5
119
0
6
Order By: Relevance
“…Levels of VEGF and bFGF proteins were calculated as nanograms of VEGF or picograms of bFGF/10 6 cells as described. 26,27 These CM were used in proliferation assays and migration assays. Preliminary experiments confirmed that the VEGF ELISA kit detected both VEGF 121 and VEGF 165 .…”
Section: Elisa and Western Blot Analysesmentioning
confidence: 99%
“…Levels of VEGF and bFGF proteins were calculated as nanograms of VEGF or picograms of bFGF/10 6 cells as described. 26,27 These CM were used in proliferation assays and migration assays. Preliminary experiments confirmed that the VEGF ELISA kit detected both VEGF 121 and VEGF 165 .…”
Section: Elisa and Western Blot Analysesmentioning
confidence: 99%
“…Cells from the human lung adenocarcinoma cell line PC14PE6 were kindly donated by Dr. Isaiah J. Fidler (20). The cells were maintained in RPMI 1640 supplemented with 10% fetal bovine serum and penicillin-streptomycin and were cultured in a humidified CO 2 incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…For production of lung metastases, human lung adenocarcinoma PC14PE6 cells (1 ϫ 10 6 ) were suspended in 0.2 mL of PBS and injected into the tail vein of nude mice (20). For evaluation of apoptosis of tumor and endothelial cells, animals received cisplatin (6 mg/kg i.v.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF is also known as vascular permeability factor, and can induce vascular leakage and may be involved brain edema (Ferrara et al, 2003). Malignant pleural effusions from lung cancer have high levels of VEGF, and VEGF secretion has also been associated with the development of ascites (Senger et al, 1983;Yanagawa et al, 1999;Yano et al, 2000a). The direct role VEGF has in angiogenesis and other malignant processes made it an attractive target for the development of new therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%